Tehnološko modeliranje energetskih procesov: Zbirka laboratorijskih vaj - Brinovar , Iztok; Igrec, Dalibor (2022)
Technological Modelling of Power Processes: Collection of Laboratory Exercises. The collection of laboratory exercises is intended primarily for first-year students of the master's study programme at the Faculty of Energy Technology, University of Maribor, as additional teaching material in implementing laboratory exercises within the course Technological Modelling of Power Processes. It is also directly related in content to the corresponding computer exercises. The exercises are designed to experiment with different systems or processes, modelling and evaluating mathematical models. In this way, students improve their knowledge and understanding of the mechanisms of operation of the processes and, through practical work, learn about the entire cyclical modelling process, which includes performing measurements, as well as making and using mathematical models. The collection of laboratory exercises in connection with computer exercises and lectures connects the discussed topic into a complete whole.
Keywords: laboratory exercises; measurements; modelling; dynamic systems; electromechanical systems